2020
DOI: 10.3390/ijerph17176312
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a Diabetes Education Program to Reduce Health Disparities in South Texas: Application of the RE-AIM Framework for Planning and Evaluation

Abstract: Health disparities in diabetes management and control are well-documented. The objective of this study is to describe one diabetes education program delivered in the United States in terms of the RE-AIM (Reach, Effectiveness, Adoption, Implementation, and Maintenance) Planning and Evaluation Framework. Questionnaires, clinical data, and administrative records were analyzed from 8664 adults with diabetes living in South Texas, an area characterized by high health disparities. The Diabetes Education Program deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…As reported in other studies, maintenance at the individual and setting levels was challenging among the RE-AIM elements [ 31 ]. Our findings showed that the HSTAP was associated with improved participants’ health outcomes at 6 months and household environment and behaviors at 9–12 months after implementing the intervention.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…As reported in other studies, maintenance at the individual and setting levels was challenging among the RE-AIM elements [ 31 ]. Our findings showed that the HSTAP was associated with improved participants’ health outcomes at 6 months and household environment and behaviors at 9–12 months after implementing the intervention.…”
Section: Discussionmentioning
confidence: 87%
“…The RE-AIM model has been widely used in various research areas, including public health, health behavior change, and individual, clinical, organizational, and community settings [ 12 ]. For example, a recent study applied the RE-AIM model to present the process and outcomes of a diabetes education program implemented in South Texas [ 14 ]. Another research revealed that RE-AIM could be an effective model for planning and assessing clinical and community-based projects [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…More than 40% of DM patients are unable to undergo therapy and healthy lifestyle modifications according to the recommendations of health workers (Pratiwi et al, 2018;Shetty et al, 2021). Several previous studies have shown that mobile health-based DM treatment is effective in reducing hbA1c levels and improving self-management of DM patients (Faroqi et al, 2018;Ory et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The CBHEC provides community-based educational and support programs that consist of diabetes management interventions, prevention activities, and clinical support in the south Texas region. 22 Recognized by the American Diabetes Association (ADA), the DSMES program offered by the CBHEC helps patients diagnosed with diabetes self-manage by learning practical strategies for making healthy lifestyle choices. The program also teaches those with prediabetes or at risk of developing diabetes to prevent or delay the onset of the disease.…”
Section: Methodsmentioning
confidence: 99%